STRATEGIES FOR PREVENTING EXPOSURE TO RADICAL IDEOLOGIES AMONG INMATES IN MEDIUM-SECURITY PRISONS AT THE SURABAYA CLASS I PRISON - Muhammad Nur Fauzi; Syahrial Yuska (Universitas Nusa Cendana, 2026)
This study analyzes strategies to prevent radicalization among terrorism convicts at the Class I Surabaya Correctional Facility using the Situational Crime Prevention approach. The research employs a qualitative method, with data collected through interviews with correctional officers and terrorism convicts, as well as document analysis. The findings show that prevention strategies are implemented through four main approaches: increasing the effort required to engage in radical activities, increasing the risk of detection, reducing provocations, and removing justifications for such behavior. In practice, these strategies are reflected in strict surveillance, the separation of terrorism convicts in special housing blocks, and the provision of moderate religious guidance to counter radical ideologies. Although these efforts have contributed to controlling the spread of radicalization, the study highlights the need for further improvements. Strengthening collaboration with external institutions, enhancing officer training, and expanding rehabilitation programs are essential steps to reduce tension, manage inmate behavior more effectively, and support successful deradicalization within correctional facilities. Keywords: Radicalization Prevention; Terrorism Convicts; Situational Crime Prevention